Use of probiotics in diets of wild-type chickens and its effects on performance - Valentim, Jean Kaique; Paula, Karynne Luana Chaves De; Geraldo, Adriano; Miranda, Diogo Alvarenga; Lemke, Sara Santana Ramos; Oliveira, Marllon José Karpeggiane De; Oliveira, Jeferson Éder Ferreira De (UFBA - Universidade Federal da Bahia, 2018)
SUMMARY The objective of this study was to evaluate the performance of male colonial chickens fed diet supplemented with commercial probiotic (Calsporin ®). A total of 210 male chicks Label Rouge lineage were used and they were raised in experimental shed up to 30 days old. These birds had free access to the pickets of Tifton-85, from 31-90 days of age. The experimental design was completely randomized, two treatments, one containing feed supplemented with probiotic Bacillus subtillis (300 g t-1 Bacillus subtillis 1×109 UFCg-1) and another one without it, with ten replications per treatment, consisting of 21 chickens/replication. The mean of body weight (BW), weight gain (WG), feed intake (FI), feed conversion (FC), mortality and viability were evaluated. The data were submitted to variance analysis and the averages of the treatments were compared by the F-test at 5% of significance. The addition of probiotic (300 g t-1 Bacillus subtillis 1×109 UFCg-1) in the diet of Label Rouge broilers did not interfere in the MW, WG, and FC variables in the total period from 1 to 90 days (P>0.05); the MFI variable differed (P <0.05), with higher consumption in chickens receiving the diet with the probiotic. The inclusion of probiotic in the wild-type chicken ration did not improve the productive performance of poultries possibly due to a low challenge by pathogenic microorganisms in the environments in which they were raised.

RESUMO Objetivou-se com este estudo avaliar o desempenho de frangos coloniais machos alimentados com ração suplementada com probiótico comercial (Calsporin ®). Foram utilizados 210 pintos de corte machos da linhagem Label Rouge, e foram criados em galpão experimental até os 30 dias de idade. Estas aves tiveram livre acesso aos piquetes de Tifton-85 (Cynodon spp.) dos 31 aos 90 dias de idade. O delineamento experimental utilizado foi inteiramente casualizado, dois tratamentos, um contendo ração suplementada com probiótico Bacillus subtillis (300 g t-1 Bacillus subtillis 1×109 UFCg-1) e outro sem suplementação, com dez repetições cada, constando 21 aves/repetição. Foram avaliados o peso corporal médio (PM), ganho de peso (GP), consumo de ração (CR), conversão alimentar (CA), mortalidade e viabilidade. Os dados foram submetidos à análise de variância, e as médias dos tratamentos foram comparadas pelo teste F a 5% de significância. A adição do probiótico (300 g t-1 Bacillus subtillis 1×109 UFCg-1) na dieta de frangos Label Rouge não interferiu nas variáveis GP, PM, e CA no período total de 1 a 90 dias (P>0,05); a variável CMR diferiu (P<0,05), sendo maior o consumo em aves recebendo a dieta com o probiótico. A inclusão de probiótico na ração de frangos caipiras não melhorou o desempenho produtivo das aves possivelmente devido a um baixo desafio por microorganismos patogênicos nos ambientes em que foram criados.
Uso de probiótico em dietas de frangos tipo caipira e seus efeitos sobre o desempenho
Keywords: alternative breeding; bacillus subtillis; peeled neck; wild-type chickens; aves caipira; Bacillus subtillis; criação alternativa; pescoço pelado